Infusion of Sibling Marrow in a Patient with Purine Nucleoside Phosphorylase Deficiency Leads to Split Mixed Donor Chimerism and Normal Immunity - Yeates, Laura; Slatter, Mary A.; Gennery, Andrew R. (Frontiers in Pediatrics, 2017)
Purine nucleoside phosphorylase (PNP) deficiency, a rare autosomal recessive metabolic disease causes combined immunodeficiency and developmental delay, hypotonia, and spasticity. Patients present with recurrent infections associated with T-lymphocytopenia, characteristically presenting later than patients with classical severe combined immunodeficiency (SCID). Purine nucleoside phosphorylase, with adenosine deaminase (ADA), is part of the purine salvage pathway. The only curative therapy is haematopoietic stem cell transplantation. Myeloablative conditioning is recommended to prevent rejection caused by residual immune function. However, HLA-identical sibling stem cell infusions in ADA-SCID result in some donor stem cell engraftment and long-term thymopoiesis. We report a patient with PNP deficiency, who received HLA-identical sibling marrow without chemotherapy because of disseminated cytomegalovirus infection. The patient presented at 14 months of age following recurrent infections, from early infancy, with persistent irritability, developmental delay and hypotonia. She had neutropenia, pan-lymphocytopenia and hypogammaglobulinaemia with low plasma urate and erythrocyte PNP activity. Diagnosis was confirmed with a homoxygous mutation in PNP. The patient was viraemic with cytomegalovirus (CMV) detected in blood and CSF by PCR. Dual anti-viral therapy improved the clinical condition and reduced the viral load. In view of the disseminated CMV infection, the decision was made to infuse stem cells without any pre-conditioning chemotherapy. She received a matched sibling donor unconditioned stem cell infusion at 16 months of age. The post-transplant course was uneventful. Blood PCR became negative for CMV. Global hypotonia persisted, although with significant improvement in irritability. At 4 years of age and 29 months post-transplant the patient demonstrated normal T-lymphocyte and Natural Killer cell numbers. Recent thymic emigrants represented 12% of the total T-lymphocyte population. Lymphocyte proliferative responses to phytohaemagluttinin were normal. Memory and class-switched B-lymphocytes were present. Immunoglobulin replacement had been discontinued, and there were normal IgG responses to tetanus vaccine, Haemophilus influenzae type B and pneumococcal conjugate vaccine antigens. There was 93% donor T-lymphocytes, 20% donor B-lymphocytes and 5% donor myeloid cells, indicative of some donor stem cell engraftment. There was no significant infection history despite regular nursery attendance. Height and weight were following the 50th centile. Split mixed donor chimerism has corrected the immunological defect.